Films containing polymeric elements that interconnect particles

Thermally induced phase separation methods enable the integration of fragile particles into polymer films, achieving low dielectric constant and high mechanical strength films suitable for automotive radar applications.

JP7599436B2Active Publication Date: 2024-12-133M INNOVATIVE PROPERTIES CO
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021567911
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-15
Filing Date
2020-05-12
Publication Date
2024-12-13
Estimated Expiration
2040-05-12

Smart Images

  • Figure 0007599436000011
    Figure 0007599436000011
  • Figure 0007599436000012
    Figure 0007599436000012
  • Figure 0007599436000013
    Figure 0007599436000013
Patent Text Reader

Abstract

The film includes a polymeric material and a plurality of particles dispersed therein. The polymeric material includes a plurality of elongated polymer elements oriented along substantially the same first direction and interconnecting the particles. An elongated end portion of at least one first elongated polymer element of the plurality of elongated polymer elements is adapted to and bonded to a first particle of the plurality of particles along the entire length of the elongated end portion. An elongated middle portion of at least one second elongated polymer element of the plurality of elongated polymer elements is adapted to and bonded to a second particle of the plurality of particles along the entire length of the elongated middle portion, the second elongated polymer element extending from both ends of the elongated middle portion in a direction away from the second particle. Multilayer films and methods are also described.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] The film may include particles dispersed in a polymeric binder. Summary of the Invention

[0002] In some aspects herein, a film is described that includes a polymeric material and a plurality of particles, the polymeric material including a plurality of elongated polymer elements having an anisotropic orientation distribution and interconnecting the particles.

[0003] In some embodiments herein, a film is provided that includes a polymeric material and a plurality of particles dispersed therein. The polymeric material includes a plurality of elongate polymeric elements that are oriented along substantially the same first direction and interconnect the particles. An elongate end portion of at least one first elongate polymeric element of the plurality of elongate polymeric elements is adapted to and bonded to a first particle of the plurality of particles along the entire length of the elongate end portion. An elongate mid portion of at least one second elongate polymeric element of the plurality of elongate polymeric elements is adapted to and bonded to a second particle of the plurality of particles along the entire length of the elongate mid portion, the second elongate polymeric element extending from both ends of the elongate mid portion in a direction away from the second particle.

[0004] In some embodiments herein, a film is provided that includes a polymeric material and a plurality of particles dispersed therein at a volumetric capacity of greater than about 50 percent. The polymeric material includes a plurality of elongated polymer elements that interconnect the particles. Each of the plurality of elongated polymer elements of a portion of the plurality of elongated polymer elements includes a plurality of spaced apart elongated portions. Each of the plurality of spaced apart elongated portions conforms to and bonds with one of the plurality of particles along the entire length of the elongated portion, and the polymeric element extends from both ends of the elongated portion in a direction away from the particles.

[0005] In some embodiments herein, a multilayer film is provided that includes a porous intermediate layer disposed between and bonded to opposing non-porous first and second protective layers. The porous intermediate layer comprises a plurality of elongated polymer elements interconnecting a plurality of hollow particles, and a plurality of interconnected voids defined by the plurality of elongated polymer elements and the hollow particles. The real part of the dielectric constant of the film at a frequency of about 2.5 GHz is less than about 1.4.

[0006] In some embodiments herein, a multilayer film is provided that includes an intermediate layer disposed between and bonded to opposing first and second protective layers. The intermediate layer includes a plurality of elongated polymer elements interconnecting a plurality of particles. For at least one pair of first and second particles of the plurality of particles, and for each elongated polymer element in a portion of the plurality of elongated polymer elements, a first end of the element terminates at the first particle and an opposite second end of the element terminates at the second particle.

[0007] In some embodiments herein, a multilayer film is provided that includes an intermediate layer disposed between and bonded to opposing first and second layers. The intermediate layer includes a plurality of hollow particles dispersed therein at a volumetric capacity of greater than about 50 percent. The multilayer film has an elongation at break of at least 15% at room temperature at a tensile load rate of about 5 Newtons per second or less. Bending the multilayer film at a bending position with an inner radius of up to 1.5 mm results in little or no damage to the intermediate layer at the bending position.

[0008] In some aspects herein, a method of making a film is provided. The method includes inducing phase separation of a polymer from a component that is a solvent for the polymer at a higher temperature but is not a solvent for the polymer at a lower temperature, such that the polymer forms a plurality of elongated polymer elements having an anisotropic orientation distribution. In some embodiments, the film includes a plurality of particles, and the plurality of elongated polymer elements interconnect the particles.

[0009] In some embodiments herein, a method of making a film is provided. The film includes a polymer and a plurality of particles dispersed therein at a volumetric capacity of more than about 50 percent. The method includes providing a mixture at a first temperature, the mixture including a plurality of particles, a polymer, and a component that is a solvent for the polymer at a higher second temperature but is not a solvent for the polymer at a lower first temperature, disposing the mixture between a first and a second release surface, heating the mixture to a second temperature, applying a first pressure to the mixture, cooling the mixture to induce phase separation of the polymer from the component, and separating the mixture from at least one of the first and the second release surfaces. The mixture is under a first pressure at the second temperature for at least one first time interval before cooling the mixture. The first pressure is high enough to cause the polymer to flow.

[0010] In some embodiments herein, a method for making a film is provided. The film comprises a polymer and a plurality of particles dispersed therein at a volumetric capacity of more than about 50 percent. The method includes providing a plurality of particles, a polymer, and a component that is a solvent for the polymer at a second higher temperature but is not a solvent for the polymer at a first lower temperature; extruding the plurality of particles, the polymer, and the component into a stream at the second temperature; passing the stream through a nip; and cooling the stream to a first temperature to induce phase separation of the polymer from the component, the nip applying pressure to the stream before or during phase separation, and inducing cooling.

[0011] In some embodiments herein, a method of making a film is provided. The film comprises a plurality of elongated polymer elements interconnecting a plurality of particles. The method comprises: 4providing a polymer having a number average molecular weight of greater than 100 g / mol and a component that is a solvent for the polymer at a higher, second temperature but not at a lower, first temperature; forming a layer comprising a plurality of particles dispersed in a miscible solution of the polymer and the component; and inducing phase separation of the polymer from the component while the layer is under pressure such that the polymer forms a plurality of elongated polymer elements. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic top view of a portion of a film. [Diagram 2] FIG. 1 is a schematic diagram of elongated polymer elements interconnecting particles. [Diagram 3] FIG. 2 is a schematic cross-sectional view of a hollow particle. [Figure 4] FIG. 2 is a schematic cross-sectional view of a coated hollow particle. [Diagram 5] FIG. 1 is a schematic cross-sectional view of a multilayer film. [Figure 6] FIG. 2 is a schematic cross-sectional view of a bent film. [Figure 7A] 1 shows a schematic of a method for making a film. [Figure 7B] 1 shows a schematic of a method for making a film. [Figure 7C] 1 shows a schematic of a method for making a film. [Figure 7D] 1 shows a schematic of a method for making a film. [Figure 7E] 1 shows a schematic of a method for making a film. [Figure 7F] 1 shows a schematic of a method for making a film. [Figure 8] FIG. 1 is a schematic diagram of a method for producing a film. [Figure 9] 1 is a scanning electron microscope (SEM) image of a portion of the film. [Figure 10] 1 is a scanning electron microscope (SEM) image of a portion of the film. [Figure 11] 1 is a plot of tensile stress versus tensile strain for various films. [Figure 12] 1 is a plot of the dielectric constant of various films versus frequency. [Figure 13] 1 is a plot of measured transmission loss through various structures. [Figure 14] 1 is a plot of calculated transmission loss through various structures. [Figure 15] 1 is a plot of the reflection coefficient calculated from various structures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the following description, reference is made to the accompanying drawings which form a part hereof, and in which various embodiments are shown by way of illustration. The drawings are not necessarily to scale. It is to be understood that other embodiments are contemplated and may be made without departing from the scope or spirit of the specification. Accordingly, the following detailed description is not to be construed in a limiting sense.

[0014] It may be desirable to load a polymer layer with fragile (e.g., mechanically weak) particles at high loadings. For example, it may be desirable to load a polymer film with glass bubbles to lower the dielectric constant of the film. However, glass bubbles or other fragile particles cannot withstand the high pressures used in traditional film processes, such as, for example, extrusion. According to some embodiments, the methods described herein can be used to provide high volumetric loadings of glass bubbles or other fragile particles within a polymer layer.

[0015] According to some embodiments, the methods described herein allow for the utilization of virtually any available polymer to bond the particles together, thereby imparting high strength to the resulting film. The particles may be brittle or other types of particles may be utilized depending on the desired application.

[0016] In some embodiments, the particles are hollow (e.g., glass bubbles) particles that have a low dielectric constant, e.g., due to a large volume fraction occupied by air. In some embodiments, the resulting film has a low dielectric constant (e.g., real part of dielectric constant less than about 1.5, or less than about 1.4, or less than about 1.35 at frequencies of 2.5 GHz or 9.5 GHz, or over the entire frequency range of, e.g., 60 GHz to 90 GHz or 72 to 82 GHz) and / or a low tan δ (e.g., less than about 0.005, or less than about 0.004, or less than about 0.003, or less than about 0.0025, or less than about 0.002 at frequencies of 2.5 GHz or 9.5 GHz, or over the entire frequency range of, e.g., 60 GHz to 90 GHz or 72 to 82 GHz).

[0017] In some embodiments, the films herein are used to reduce transmission loss, for example, between an automotive radar unit and the exterior of the automobile. In some cases, transmission loss between the radome and air and / or between the air and the bumper material occurs due to reflections due to differences in dielectric constant between the radome and air or between the air and the bumper material. Such reflections can also result in undesirable "ghost imaging." As shown in the examples, transmission loss can be reduced, for example, by using the films herein to provide a layer having a dielectric constant intermediate between air and typical materials used in bumpers. In some embodiments, a bumper is provided that includes the films described herein. In some embodiments, a radome is provided that includes the films described herein.

[0018] As used herein, "miscibility" refers to the ability of a substance to mix (i.e., completely dissolve in each other at any concentration) in all proportions to form a solution; for some solvent-polymer systems, heat may be required for the polymer to become miscible with the solvent. In contrast, a substance is immiscible if it does not form a solution in significant proportions. For example, butanone is significantly soluble in water, but these two solvents are not miscible because they are not soluble in all proportions. In some cases, a component is a solvent for the polymer (i.e., the polymer is miscible with the component) at higher temperatures, but is not a solvent for the polymer at lower temperatures. At higher temperatures, the polymer and the component form a miscible polymer-solvent solution. When the temperature is reduced, the component is not a solvent for the polymer, and the polymer may then phase separate from the component to form a polymer network. When the phase transition is induced by a change in temperature, the phase separation may be referred to as a thermally induced phase separation (TIPS) process.

[0019] In the TIPS process, high temperature is used to turn a non-solvent into a solvent for the polymer, and then the temperature is lowered to turn the solvent back into a non-solvent for the polymer. The solvents used in the TIPS process may be volatile or non-volatile. In some embodiments herein, the film or layer in the multilayer film comprises a polymeric material that includes a plurality of elongated polymeric elements that interconnect a plurality of particles. The polymeric material and the plurality of particles may be referred to as a polymer matrix composite.

[0020] In making polymer matrix composites using the methods described herein, it has been found that slurries can be made with relatively high particle loading and can be cast into layers that maintain their morphology when the solvent component is heated and becomes miscible with the polymer. The solvents used can be volatile and can be subsequently evaporated.

[0021] In some embodiments, the methods described herein can provide relatively high particle loadings for processing into desired useful articles. Highly loaded article embodiments provided by the methods described herein can provide relatively low binder contact with filler particles and relatively highly porous articles. Such openness can significantly reduce the masking effect present in conventional particle bonding systems and can facilitate exposure of relatively high surface activity particles or active particles in porous articles to liquids or gases. In some embodiments, this openness contributes to providing low dielectric constants and low dielectric losses (e.g., in some embodiments, the phase-separated morphology of the polymeric material can provide a high volume fraction of air, which has a substantially lower dielectric constant than the polymeric material).

[0022] Previous methods of making films using TIPS can be divided into two groups: active and passive. In the active method, the particles, binder polymer, and its solvent are actively mixed at high temperature to dissolve the polymer (which may be provided as polymer particles) in the solvent, and the blend is molded into the desired form factor by hot pressing (e.g., on a laboratory scale) or by extruding through a heated die (e.g., on a large or manufacturing scale). The hot film in its final form is quenched to a lower temperature at which phase separation occurs. In the passive method, the particles, binder polymer, and binder polymer solvent are mixed at room temperature, the slurry is molded into its desired form factor by first coating between two liners or filling a predefined cavity, and the film is cured in an oven to dissolve the polymer in the solvent. The hot film is then quenched to a lower temperature so that phase separation occurs.

[0023] The active method allows for homogeneous mixing of the polymers and allows for substantially complete disentanglement of the polymer chains, thereby allowing for substantially complete utilization of the available polymer. The method also allows for the raw materials to be fed directly into the extruder. However, this method has some important limitations: First, only a few solvents preferably have low vapor pressure (e.g., mineral oil) and / or high boiling points, so it may be necessary to extract the solvent from the film by solvent extraction methods. Second, slurries containing dissolved polymers are usually highly viscous, and high pressures are usually required to mold the slurry into the desired form factor. Thus, the active method is typically not suitable for the use of fragile particles (e.g., glass bubbles) that are susceptible to mechanical pressure. The high pressure and shear applied during the extrusion process may result in mechanical breakage of the particles, or loss of desired properties, for example, due to the strain induced during extrusion.

[0024] Passive methods allow for the use of high vapor pressure solvents, are susceptible to multiple solvents that may readily volatilize in a solvent-rated oven, and eliminate the need for solvent extraction methods. Because the polymer particles are not dissolved in the solvent, the slurry can easily spread with small pressures. Therefore, this method can be used to treat particles that are susceptible to mechanical damage during processing. However, because the polymer particles are not actively mixed or agitated in the solvent, local concentration gradients may be created and the polymer particles may not completely dissolve in the solvent. Furthermore, because there is no active flow / mixing in the film, the polymer entanglement that is expected after quenching is typically not sufficient, leading to a weaker film, thereby limiting the amount of particles that can be loaded into the film.

[0025] According to the present specification, a method for making a film having the advantages of both the active and passive approaches described above is provided. After the polymer is dissolved in the coated film, by applying (e.g., small) pressure, the polymer can be forced to actively flow without damaging the particles, forming a robust film. In some embodiments, the method described herein results in a plurality of elongated polymer elements that interconnect a plurality of particles. In some embodiments, the resulting film includes a polymeric material and a plurality of particles dispersed therein at a volumetric capacity of more than about 50%, or more than about 55%, or more than about 60%, or more than about 65% (e.g., the volumetric capacity may be from about 50% to about 65%). This volumetric capacity refers to the percentage of the volume of a layer or film including the polymeric material that is occupied by the particles. Since a significant portion of the volume of the layer or film may be occupied by air, the volume % based on the volume of the particles and the polymeric material (the volume of the particles divided by the volume of the particles and the volume of the polymeric material multiplied by 100%) may be significantly higher than the volumetric capacity of the particles in the polymeric material. In some embodiments, the particle to polymer volume ratio (the ratio of the volume of the plurality of particles to the volume of the polymeric material) is at least 5, or at least 10, or at least 20, or at least 30, or at least 40. In some such embodiments, the particle to polymer volume ratio is 100 or less, or 50 or less, or 40 or less.

[0026] Typically, the maximum particle loading that can be achieved in conventional particle-filled composites (e.g., high-density polymer films and adhesives) is no more than about 40-60% by volume, based on the volume of particles and binder. Incorporating more than 60% by volume of particles into conventional particle-filled composites is not achievable because such high particle-loaded materials typically cannot be processed by coating or extrusion methods and / or the resulting composites would be very brittle. Conventional composites also typically fully encapsulate the particles with the binder, which prevents access to the particle surface and minimizes possible particle-to-particle contact. Surprisingly, the high levels of solvent and phase-separated morphology obtained by the methods described herein allow for high particle loading with a small amount of high molecular weight binder. High particle loading also helps minimize the formation of thin non-porous polymer layers that may form during phase separation. Additionally, the polymer matrix composites described herein are relatively flexible and tend not to allow particles to fall off.

[0027] Without wishing to be bound by theory, it is believed that another advantage of the polymer matrix composite embodiments described herein for some applications is that the particles are not completely coated by the binder, which allows for a high degree of particle surface contact without masking due to the porous nature of the binder. The porous nature of the composite matrix allows for hydrodynamic flow or fast diffusion through the interparticle pores. Slower diffusion transport typically occurs through the smaller pores of the porous particle media. The high open surface area of ​​the retained particles helps to reduce this slow diffusion transport effect and provide high separation power and capacity as typically seen in depth filter media. The high molecular weight binder also does not flow easily even at high temperatures (e.g., 135°C) in the absence of solvent, allowing steam sterilization. In some embodiments, the porous layer has a more uniform pore size distribution compared to conventional porous films.

[0028] In some embodiments, a film including a polymer matrix composite layer is used for its dielectric properties, as further described elsewhere herein, In some embodiments, additional layers (e.g., protective layers) are included (e.g., for improved mechanical properties) without substantially affecting the dielectric properties of the polymer matrix composite layer.

[0029] In some embodiments, the polymeric material may comprise, consist essentially of, or consist of at least one thermoplastic polymer. Exemplary thermoplastic polymers include polyurethanes, polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, and polylactic acid), polyamides (e.g., nylon 6, nylon 6,6, and polypeptides), polyethers (e.g., polyethylene oxide and polypropylene oxide), polycarbonates (e.g., bisphenol-A-polycarbonate), polyimides, polysulfones, polyethersulfones, polyphenylene oxides, polyacrylates (e.g., thermoplastic polymers formed from the addition polymerization of monomers containing acrylate functionality), polymethacrylates (e.g., methacrylates), and the like. Examples of suitable thermoplastic polymers include polyvinylidene fluoride (thermoplastic polymers formed from addition polymerization of monomers containing carboxylate functional groups), polyolefins (e.g., polyethylene and polypropylene), styrene and styrene-based random and block copolymers, chlorinated polymers (e.g., polyvinyl chloride), fluorinated polymers (e.g., polyvinylidene fluoride; copolymers of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride; copolymers of ethylene, tetrafluoroethylene, and hexafluoropropylene; and polytetrafluoroethylene), and copolymers of ethylene and chlorotrifluoroethylene. In some embodiments, the thermoplastic polymer includes a homopolymer or a copolymer (e.g., a block copolymer or a random copolymer). In some embodiments, the thermoplastic polymer comprises a mixture of at least two thermoplastic polymers (e.g., a mixture of polyethylene and polypropylene, or a mixture of polyethylene and polyacrylate). In some embodiments, the polymer may be at least one of polyethylene (e.g., ultra-high molecular weight polyethylene), polypropylene (e.g., ultra-high molecular weight polypropylene), polylactic acid, poly(ethylene-co-chlorotrifluoroethylene), and polyvinylidene fluoride.In some embodiments, the thermoplastic polymer is a single thermoplastic polymer (i.e., not a mixture of at least two thermoplastic polymers), hi some embodiments, the thermoplastic polymer consists essentially of or consists of polyethylene (e.g., ultra-high molecular weight polyethylene).

[0030] In some embodiments, the thermoplastic polymers used to make the films described herein are in the form of particles having a particle size of less than 1000 micrometers (in some embodiments, in the range of 1-10, 10-30, 30-100, 100-200, 200-500, 500-1000 micrometers).

[0031] In some embodiments, the polymeric material comprises at least one of polyacrylonitrile, polyurethane, polyester, polyamide, polyether, polycarbonate, polyimide, polysulfone, polyphenylene oxide, polyacrylate, polymethacrylate, polyolefin, styrene or styrenic random and block copolymers, chlorinated polymers, fluorinated polymers, or copolymers of ethylene and chlorotrifluoroethylene.

[0032] In some embodiments, the film is about 10 4 In some embodiments, the polymer or polymeric material forming the elongated polymeric elements is formed using a polymer having a number average molecular weight of more than 5×10 g / mol. 4 ~1×10 7 g / mol range (in some embodiments, 1×10 6 ~8×10 6 , 2×10 6 ~6×10 6 , or even 3×10 6 ~5×10 6For purposes herein, the number average molecular weight can be measured by techniques known in the art, such as gel permeation chromatography (GPC). GPC can be performed in a suitable solvent for the thermoplastic polymer with the use of narrow molecular weight distribution polymer standards (e.g., narrow molecular weight distribution polystyrene standards). Thermoplastic polymers are generally characterized as being partially crystalline and exhibit a melting point. In some embodiments, the thermoplastic polymer can have a melting point in the range of 120-350°C (in some embodiments, in the range of 120-300, 120-250, or even 120-200°C). The melting point of the thermoplastic polymer can be measured by techniques known in the art, such as measurement of the onset temperature in a differential scanning calorimetry (DSC) test performed with a 5-10 mg sample and a heating scan rate of 10°C / min while the sample is under a nitrogen atmosphere.

[0033] The solvent components (e.g., components that are solvents for the polymer for at least some temperatures) are selected to form a miscible polymer-solvent solution. The solvent may be a blend of at least two individual solvents. In some embodiments, when the polymer is a polyolefin (e.g., at least one of polyethylene and polypropylene), the solvent may be, for example, at least one of mineral oil, tetralin, decalin, orthodichlorobenzene, cyclohexane-toluene mixture, dodecane, paraffin oil / wax, kerosene, isoparaffin fluid, p-xylene / cyclohexane mixture (1 / 1 wt / wt), camphene, 1,2,4 trichlorobenzene, octane, orange oil, vegetable oil, castor oil, or palm kernel oil. In some embodiments, when the polymer is polyvinylidene fluoride, the solvent may be, for example, at least one of ethylene carbonate, propylene carbonate, or 1,2,3 triacetoxypropane. The solvent may be removed, for example, by evaporation. High vapor pressure solvents are particularly suitable for this removal method. However, when a first solvent has a low vapor pressure, it may be desirable to extract the first solvent with a second solvent having a higher vapor pressure, followed by evaporation of the second solvent. For example, in some embodiments, when mineral oil is used as the first solvent, hot (e.g., about 60° C.) isopropanol, or methyl nonafluorobutyl ether (C 4 F 9 OCH 3 ) and ethyl nonafluorobutyl ether (C 4 F 9 O.C. 2 H 5A blend of ethylene glycol ether (e.g., available under the trade designation "NOVEC 72DE" from 3M Company, St. Paul, MN) and trans-1,2-dichloroethylene can be used as the second solvent to extract the first solvent, followed by evaporation of the second solvent. In some embodiments, when at least one of vegetable oil or palm kernel oil is used as the first solvent, hot (e.g., about 60° C.) isopropanol can be used as the second solvent. In some embodiments, when ethylene carbonate is used as the first solvent, water can be used as the second solvent.

[0034] In some embodiments, small amounts of other additives can be added to the polymer matrix composite to impart additional functionality or to act as processing aids. These include viscosity modifiers (e.g., fumed silica, block copolymers, and waxes), plasticizers, heat stabilizers (such as those available under the trade designation "Irganox 1010" from BASF, Ludwigshafen, Germany), antimicrobial agents (e.g., silver and quaternary ammonium), flame retardants, antioxidants, dyes, pigments, and ultraviolet (UV) stabilizers.

[0035] Typically, the mixture or slurry is continuously mixed or blended to prevent or reduce settling or separation of the polymer and / or particles from the solvent. In some embodiments, the slurry is degassed using techniques known in the art to remove trapped air.

[0036] The slurry can be formed into an article (e.g., a film) using techniques known in the art, including knife coating, roll coating (e.g., roll coating through a defined nip), and coating through any number of different dies having appropriate dimensions or profiles.

[0037] In some embodiments of the methods described herein, the combining (e.g., mixing or blending the polymer, particles, and components (solvent at some temperature)) is performed at a temperature (e.g., a lower first temperature) below the melting point of the polymer and below the boiling point of the solvent.

[0038] In some embodiments of the methods described herein, the mixture (or slurry) is heated at a second higher temperature above the melting point of the miscible thermoplastic polymer-solvent solution and below the boiling point of the solvent.

[0039] In some embodiments of the method described herein, inducing phase separation is carried out at least one temperature below the melting point of the polymer in the slurry. Without wishing to be bound by theory, it is believed that in some embodiments, the solvent used to prepare the miscible blend with the polymer may cause a melting point depression in the polymer. The melting points described herein include any melting point depression of the polymer-solvent system.

[0040] In some embodiments of the methods described herein, a film or layer comprising a polymeric material comprising a plurality of elongated polymeric element structures may be formed during phase separation. In some embodiments, the polymeric material is brought about by induced phase separation of a miscible thermoplastic polymer solvent solution. In some embodiments, the phase separation is thermally induced (e.g., by thermally induced phase separation (TIPS) by quenching to a temperature lower than that used during heating). The cooling can be brought about, for example, in air, in a liquid, or at a solid interface, and may be varied to control the phase separation. The polymeric material may form a network structure that may be inherently porous (i.e., may have pores). The pore structure may be open, which allows fluid communication from an interior region of the film or layer to the outer surface of the film or layer, and / or between a first surface of the film or layer and a second surface of the film or layer opposite the first surface of the film or layer.

[0041] In some embodiments of the methods described herein, the weight ratio of solvent to polymer is at least 9:1. In some embodiments, the volume ratio of particles to polymer is at least 9:1. In some embodiments, it may be desirable to form the layer at room temperature for ease of manufacturing. Typically, during the formation of layers using phase separation, relatively small pores are particularly susceptible to collapse during solvent extraction. The relatively high particle-to-polymer loading achievable by the methods described herein can reduce pore collapse, resulting in a more uniform and defect-free polymer matrix composite.

[0042] In some embodiments of the films described herein, the particles are present in a range of 1 to 99 weight percent (in some embodiments, in a range of 15 to 99, 25 to 98, 50 to 98, 75 to 98, or even 93 to 97 weight percent) based on the total weight of the polymer matrix composite (excluding any solvent), and can vary depending, for example, on the particular particles used.

[0043] The polymeric material may interconnect the particles to form a porous network structure. The polymeric material may further include a plurality of interconnected morphologies, which may include, for example, nodules, nodes, open cells, closed cells, leafy laces, strands, nodes, spheres, or honeycombs, including elongated polymeric elements, such as polymer fibrils. The polymeric structure may directly adhere to the surface of the particles and act as a binder for the particles. In this regard, the space between adjacent particles (e.g., particles or agglomerated particles) may include a polymeric structure, as opposed to a solid matrix material, thereby providing the desired porosity.

[0044] In some embodiments, the particles are dispersed within the polymeric material such that the outer surfaces of the individual units of particles (e.g., individual particles or individual agglomerated particles) are largely free of contact or coating by the polymeric material. In this regard, in some embodiments, the average percentage area coverage of the polymeric material with respect to the outer surfaces of the individual particles (i.e., the percentage of the outer surface area that is in direct contact with the polymeric material) is 50 percent or less (in some embodiments, 40, 30, 25, 20, or even 10 percent or less), based on the total surface area of ​​the outer surfaces of the individual particles.

[0045] In some embodiments, the polymeric material does not infiltrate interior pores or the interior surface areas of the individual particles (e.g., individual particles or individual agglomerated particles) are largely not contacted or coated by the polymeric network structure.

[0046] Exemplary particles include hollow particles, acoustically active particles, soft magnetic particles, hard magnetic particles, thermally conductive particles, thermally insulating particles, intumescent particles, functional particles, dielectric particles, indicator particles, polar solvent soluble particles, polar solvent swellable particles, electrically conductive particles, or heat absorbing particles.

[0047] In some preferred embodiments, the particles are hollow particles that provide a low dielectric constant and / or low loss at a predetermined frequency or a predetermined frequency range. In some embodiments, a multilayer film is provided that includes an intermediate layer disposed between opposing outer layers, the intermediate layer including elongated polymeric elements that interconnect a plurality of particles. In some embodiments, the outer layer may be included to prevent particles from being lost from the intermediate layer, for example, when the film is subjected to abrasion. In some embodiments, the inclusion of the outer layer substantially improves the mechanical properties of the film.

[0048] 1 is a schematic top view of a portion of a film 100 including a polymeric material 110 and a plurality of particles 120 dispersed therein. The polymeric material 110 includes a plurality of elongated polymeric elements 112 oriented along substantially the same first direction 115 and interconnecting the particles 120, which may be, for example, hollow particles.

[0049] In some embodiments, the elongated end portion 113 of at least one first elongated polymer element 114 of the plurality of elongated polymer elements 112 conforms to and is bonded to a first particle 121 of the plurality of particles 120 along the entire length of the elongated end portion 113. In some embodiments, the elongated middle portion 116-1 of at least one second elongated polymer element 117 of the plurality of elongated polymer elements 112 conforms to and is bonded to a second particle 122 of the plurality of particles 120 along the entire length of the elongated middle portion 116-1, the second elongated polymer element 117 extending from both ends 116a, 116b of the elongated middle portion 116 in a direction away from the second particle 122.

[0050] In some embodiments, each elongated polymer element in a plurality (e.g., 117, 119) of the plurality of elongated polymer elements 112 includes a plurality of spaced apart elongated portions (e.g., elongated element 117 includes at least three spaced apart elongated portions 116-1, 116-2, and 116-3, and elongated element 119 includes at least three spaced apart elongated portions 118-1, 118-2, and 118-3). Each elongated portion (e.g., 116-1) of the plurality of spaced apart elongated portions conforms to and bonds with one particle (e.g., 122) of the plurality of particles 120 along the entire length of the elongated portion (e.g., 116-1), with the polymer element extending from both ends (e.g., 116a, 116b) of the elongated portion (e.g., 116-1) in a direction away from the particle 122. In some embodiments, the portion of the plurality of elongated polymer elements comprises at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50% of the plurality of elongated polymer elements 112. In some such embodiments, the portion of the plurality of elongated polymer elements comprises no more than 80%, or no more than 70%, or no more than 60% of the plurality of elongated polymer elements 112.

[0051] In some embodiments, for at least one pair of a first particle 121 and a second particle 132 in the plurality of particles 120, and for each elongated polymer element in some of the plurality of elongated polymer elements (114, 134) of the plurality of elongated polymer elements 112, a first end 133 of the element terminates at the first particle 121 and an opposite second end 135 of the element terminates at the second particle 132. In some embodiments, the elongated polymer elements in some of the plurality of elongated polymer elements are substantially parallel to one another (e.g., generally extending along the same first direction 115, but possibly having an orientation that undulates or otherwise varies somewhat about the first direction 115). In some embodiments, some of the plurality of elongated polymer elements include at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50% of the plurality of elongated polymer elements 112. In some such embodiments, the portion of the plurality of elongated polymer elements comprises 80% or less, or 70% or less, or 60% or less of the plurality of elongated polymer elements 112 .

[0052] The spaces between the elongated polymeric elements 112 may be at least partially filled (e.g., filled with) a material 143, which may be, for example, air or oil. In some embodiments, the film 100 is produced by providing a plurality of particles 120, a polymer, and a component (e.g., oil) that is a solvent for the polymer at a higher second temperature but not at a lower first temperature, and inducing phase separation of the polymer from the component while the layer is under pressure, such that the polymer forms a plurality of elongated polymeric elements 112. In some such embodiments, the material 143 is the component. In other embodiments, the component is removed and the material 143 is air or another material that is added to the spaces after the component is removed.

[0053] In some embodiments, a plurality of interconnected voids 147 are defined by a plurality of elongated polymeric elements 112 and particles 120, which may be hollow particles.

[0054] In some embodiments, the polymeric material 110 is about 10 4 g / mol or any of the ranges described elsewhere. In some embodiments, the polymer is or includes, for example, ultra-high molecular weight polyethylene (UHMWPE). In some embodiments, the particles of the plurality of particles 120 are dispersed in the polymeric material 110 at a volumetric volume of greater than about 50 percent, or any of the ranges described elsewhere. In some embodiments, the ratio of the volume of the plurality of particles 120 to the volume of the polymeric material 110 is at least 4, or the ratio can be any of the ranges described elsewhere.

[0055] In some embodiments, the plurality of elongated polymeric elements have an anisotropic distribution of orientation (eg, the elongated polymeric elements within a film or layer may have a substantial directionality in the plane of the film or layer).

[0056] The polymeric material 110 includes a plurality of elongated polymeric elements 112 that are oriented along substantially the same first direction 115 (e.g., generally extending along the first direction 115, but possibly having an orientation that undulates or otherwise varies somewhat about the first direction 115) and interconnect the particles 120. In some embodiments, a portion of the film 100 that includes the polymeric material 110 and a plurality of particles 120 dispersed therein has a dimension that is substantially greater than the average center-to-center spacing between the particles 120 (e.g., each of the length and width of the portion can be at least 4 times, at least 6 times, or at least 10 times the average center-to-center spacing between the particles 120). In some embodiments, the elongated polymeric elements of the portion extend along substantially the same first direction. In such cases, the film may be described as including a polymeric material (the polymeric material within the portion) and a plurality of particles (the particles within the portion) dispersed therein, the polymeric material including a plurality of elongated polymeric elements that are oriented along substantially the same first direction and interconnect the particles. In some embodiments, the elongated polymeric elements throughout the film extend along substantially the same first direction, hi some embodiments, the elongated polymeric elements throughout the film extend substantially radially from a location within the film (e.g., near the center).

[0057] In some embodiments, the film includes a polymeric material extending between the elongated polymeric elements 112. The polymeric material may define polymeric elements extending laterally between the elongated polymeric elements. In some cases, the polymeric material includes a morphology such as, for example, leafy lace, strands, or mesh. In some embodiments, the plurality of elongated polymeric elements and any polymeric material extending laterally between the elongated polymeric elements define a plurality of interconnected pores. The interconnected pores may be filled with oil (e.g., in embodiments where the solvent component is not removed) or may be filled with air (e.g., in embodiments where a low dielectric constant is desired).

[0058] In some embodiments, the elongate polymer elements have a length that is substantially greater than their width. For example, in some embodiments, the elongate polymer elements have a length that is at least 2, 5, 10, or 20 times their average width. In some embodiments, the elongate polymer elements are polymer fibrils (e.g., polymer microfibrils). In some embodiments, the individual elongate polymer elements or individual polymer fibrils have an average width in the range of 10 nm to 100 nm (in some embodiments, in the range of 100 nm to 500 nm, or even 500 nm to 5 micrometers).

[0059] 2 is a schematic diagram of an elongated polymer element 217 and particles 221, 222, and 223. In some embodiments, each elongated polymer element 217 in at least some of the plurality of elongated polymer elements extends from at least a first particle 221 of one of the plurality of particles beyond the next-nearest neighbor 223 of the first particle 221 along the elongated polymer element 217. In the illustrated embodiment, the elongated polymer element includes elongated portions 213, 216-1, and 216-2. The elongated portion 213 includes an end 233 of the elongated polymer element 217. The elongated portion 213 is conformed to and bonded to the first particle 221 along the entire length of the elongated portion 213 between the end 233 and both ends 213a of the elongated portion 213. The elongated portion 216-1 is conformed to and bonded to the nearest neighbor 222 of the first particle 221 along the elongated polymer element 217. The polymer element 217 extends from both ends 216-1a, 216-1b of the elongated portion 216-1 in a direction away from the particle 222. Similarly, the elongated portion 216-2 is conformed to and bonded to the next-nearest adjacent particle 223 of the first particle 221 along the elongated polymer element 217. The polymer element 217 extends from both ends 216-2a, 216-2b of the elongated portion 216-2 in a direction away from the particle 223. The elongated portion 213 may be referred to as an elongated end portion, and the elongated portions 216-1 and 216-2 may be referred to as an elongated middle portion.

[0060] In the illustrated embodiment, the elongated polymer element 217 extends from a first particle 221 of the plurality of particles, beyond the next-nearest particle 223 of the first particle 221 along the elongated polymer element 217. In other cases, the elongated portion 213 may not terminate at the first particle 221, but may instead extend from both ends of the elongated portion in a direction away from the first particle 221 (see, for example, the elongated element 117 shown in FIG. 1). In such cases, the elongated polymer element 217 extends at least from the first particle 221 of the plurality of particles, beyond the next-nearest adjacent particle 223 of the first particle 221 along the elongated polymer element 217.

[0061] In some embodiments, the plurality of particles (e.g., the plurality of particles 120) comprises hollow particles. For example, at least 50%, or at least 70%, or at least 90%, or all or substantially all of the particles 120 can be hollow. In some embodiments, a particle of the plurality of particles 120 is hollow. In some embodiments, the plurality of particles 120 comprises frangible particles (e.g., hollow glass beads). In some such embodiments, the film 100 includes additional particles that are not hollow. In some embodiments, the hollow particles comprise hollow glass beads, hollow ceramic particles, or a combination thereof.

[0062] FIG. 3 is a schematic cross-sectional view of a hollow particle 321 that includes a shell 338 that may, for example, surround an air pocket 339 .

[0063] Particle 321 has a diameter D. In some embodiments, the particles of the plurality of particles are hollow and have an average size D of greater than about 1 micron, or greater than about 5 microns, or greater than about 10 microns. In some embodiments, D is less than about 500 microns, or less than about 200 microns, or less than about 150 microns, or less than about 100 microns. The average size of the plurality of particles is measured, for example, by a median diameter D as measured by particle size analysis. 50The average lateral spacing between the elongated polymer elements can be measured as, for example, the average size D, or less than 0.5D, or less than 0.3D. In some such embodiments, or in other embodiments, the average lateral spacing between the elongated polymer elements is at least 1.5 times, or at least 2 times, or at least 3 times the average width of the elongated polymer elements. The particle size can be monodisperse or polydisperse. In some embodiments, the particles are spherical or substantially spherical. In other embodiments, particles having other shapes can be used.

[0064] Suitable particles include glass bubbles, such as soda lime borosilicate glass particles. Suitable soda lime borosilicate glass bubbles include 3M Glass Bubbles S32HS and 3M Glass Bubbles K1, both available from 3M Company, St. Paul, Minn.

[0065] FIG. 4 is a schematic cross-sectional view of a hollow particle 421 including a shell 438 that may, for example, enclose an air pocket 439. A coating 440, 441 is applied to the shell 438. In the illustrated embodiment, the coating 440, 441 includes two coating layers 440 and 441. In other embodiments, one coating layer is included. In still other embodiments, three or more coating layers are included. In some embodiments, at least a majority of the hollow particles include a coating 440, 441 on an outer surface of the hollow particle. In some embodiments, the outermost layer (e.g., layer 440) is a surface treatment layer applied to the particle. In some embodiments, the coating includes a metal layer (e.g., layer 441). The metal layer may include, for example, copper, aluminum, silver, tungsten, or a combination thereof. In some embodiments, the coating further includes an inorganic insulating layer (e.g., layer 440) disposed on the metal layer (e.g., layer 441) on the outer surface. The insulating layer may be or include, for example, alumina. In other embodiments, the particles 421 may be solid particles that may be coated with one or more layers. A metal coating with an inorganic insulating coating may be included on the particles (hollow or solid) to, for example, change the dielectric properties of a layer containing the particles without making the layer conductive. Polymer matrix composites containing dielectric particles are described, for example, in WO 2019 / 099603 (Veeraraghavan et al.) and corresponding U.S. Provisional Patent Application Publication No. 62 / 587045, filed November 16, 2017, entitled "Polymer Matrix Composites Comprising Dielectric Particles and Methods of Making the Same."

[0066] In some embodiments, the particles include a surface treatment, for example to improve adhesion to polymers. Suitable surface treatments include silane surface treatments. In some embodiments, the silane includes one or more functional groups, such as, for example, vinyl or alkyl groups.

[0067] In some embodiments, the particles are hollow glass microspheres, for example made from soda-lime borosilicate. In some embodiments, at least a portion of the alkali ions of the hollow particles can be extracted with an acid, for example to improve dielectric properties. For example, sodium or other alkali metal ions tend to increase the dielectric constant and loss tangent of the particles. Acid extraction can be used to reduce the dielectric constant and / or loss tangent of the particles, as well as the dielectric constant and / or loss tangent of a porous layer incorporating the particles. Acid extraction can be applied to the particles before incorporating the particles into the porous layer, or acid extraction can be applied to the porous layer containing the particles, since the porous nature of the layer allows the acid to reach the surface of the particles. In embodiments where acid extraction is applied to the porous layer, the extractables can be removed from the porous layer, for example, by a rinsing process.

[0068] 5 is a schematic cross-sectional view of a multilayer film 550 including an intermediate layer 500 disposed between and bonded to opposing first and second layers 546 and 548. The intermediate layer 500 may correspond to any film described herein, for example, including elongated polymer elements interconnecting a plurality of particles. The intermediate layer 500 may correspond to film 100, for example. In some embodiments, the intermediate layer 500 is porous and the first and second layers 546 and 548 are non-porous. In some embodiments, the first and second layers 546 and 548 are protective layers (e.g., polymer films). In some embodiments, one of the first and second layers 546 and 548 is a protective polymer film and the other of the first and second layers 546 and 548 is an adhesive layer. The adhesive layer may also function as a protective layer.

[0069] In some embodiments, the multilayer film 550 includes a porous intermediate layer 500 disposed between and bonded to opposing non-porous first and second protective layers 546 and 548, the porous intermediate layer 500 including a plurality of elongated polymeric elements interconnecting a plurality of hollow particles, and including a plurality of interconnected voids defined by the plurality of elongated polymeric elements and the hollow particles. In some embodiments, the real part of the dielectric constant of the film 550 at a frequency of about 2.5 GHz (or other frequency or frequency range described elsewhere) is less than about 1.4 or any range described elsewhere. In some embodiments, the ratio of the imaginary part to the real part of the dielectric constant of the film 550 at a frequency of about 2.5 GHz (or other frequency or frequency range described elsewhere) is less than about 0.004 or any range described elsewhere. In some embodiments, the particles of the plurality of particles are dispersed in the porous intermediate layer 500 by a volumetric volume of greater than about 50 percent or any range described elsewhere. In some embodiments, the ratio of the volume of the plurality of particles to the volume of the polymeric material in intermediate layer 500 is at least 4, or the ratio can be any of the ranges described elsewhere.

[0070] In some embodiments, the film or multilayer film has an elongation at break of at least 3%, or at least 5%, or at least 7%, or at least 10%, or at least 12%, or at least 15%, at room temperature (e.g., about 20° C. or about 25° C.) and at a tensile loading rate of about 5 Newtons per second or less (e.g., a rate of 5 N / s or a rate of 1 N / s).

[0071] In some embodiments, the multilayer film 550 includes an intermediate layer 500 disposed between and bonded to opposing first and second protective layers 546 and 548, the intermediate layer 500 including a plurality of hollow particles dispersed therein at a volumetric capacity of greater than about 50 percent. In some such embodiments, the multilayer film has an elongation at break of at least 15% at room temperature at a tensile load rate of about 5 Newtons per second or less. In some such embodiments, bending the multilayer film at a bending position with an inner radius of up to 1.5 mm results in little or no damage to the intermediate layer at the bending position. Damage to the intermediate layer at the bending position can be determined by viewing the multilayer film before and after bending the film. The phrase "very little damage to the intermediate layer" means that the bending resulted in, at most, slight, barely visible cracks in the intermediate layer.

[0072] In some embodiments, layers 546 and 548 are films (e.g., polyethylene films) that are laminated to layer 500. In some embodiments, layers 546 and 548 are sealing layers that are applied to layer 500. For example, the sealing layer can be applied as some polymer (e.g., acrylate) dissolved in a solvent, or as a monomer dissolved in a solvent that is later polymerized (e.g., by exposure to UV light or heat curing), or can be applied by, for example, extrusion lamination.

[0073] 6 is a schematic cross-sectional view of a film 650 (e.g., corresponding to film 100 or multilayer film 550) bent at bend location 653 about an inner radius R. In some embodiments, R is up to 1.5 mm.

[0074] 7A-7F show a method of manufacturing a film. In some embodiments, the method includes providing a mixture 760 at a first temperature (e.g., room temperature). The mixture includes a plurality of particles, a polymer, and a component that is a solvent for the polymer at a higher second temperature, but is not a solvent for the polymer at the lower first temperature. At the first temperature, the mixture 760 may be described as a slurry. As shown generally in FIG. 7B, the method includes disposing the mixture 760 between a first release surface 761 and a second release surface 762, which may be, for example, the surface of a release film. As shown generally in FIG. 7C, the method includes heating the mixture 760 to a second temperature (e.g., using hot plates 763 and 764, as shown generally in FIG. 7C). The polymer and the component then form a miscible polymer-solvent solution, and the plurality of particles, if included, are dispersed in the solution. As shown generally in FIG. 7D, the method further includes applying a first pressure (e.g., greater than atmospheric pressure) to the mixture 760. In the illustrated embodiment, the mixture with the liner is placed between additional plates 766 and 767, and a spacer 768 is used to separate the plates 766 and 767. As shown generally in FIG. 7E, the method further includes cooling the mixture to induce phase separation of the polymer from the components. In the illustrated embodiment, cooling plates 773 and 774 are utilized. As shown generally in FIG. 7F, the method further includes separating the mixture from at least one of the first release surface 761 and the second release surface 762. In the illustrated embodiment, both release surfaces 761 and 762 are removed. During at least one first time interval (e.g., 1-10 minutes) prior to cooling the mixture, the mixture is under a first pressure at a second temperature, the first pressure being sufficiently high to cause the polymer to flow. An appropriate pressure to cause the polymer to flow may depend, for example, on the temperature and molecular weight of the polymer. In some embodiments, the resulting film 700 includes a polymer and a plurality of particles dispersed therein at a volumetric capacity of greater than about 50 percent.In some embodiments, the resulting film has a ratio of the volume of the plurality of particles to the volume of the polymeric material of at least 4, or the ratio can be in any of the ranges described elsewhere.

[0075] In some preferred embodiments, the method further comprises removing the component, or at least a portion of the component, to provide a film. In some embodiments, the film may comprise the component.

[0076] 7A-7F may be performed sequentially. In some embodiments, the heating step is performed prior to the application of the first pressure, and the application of the first pressure is performed while the mixture is at the second temperature.

[0077] In some embodiments, cooling the mixture to induce phase separation includes cooling the mixture to a first temperature. In some embodiments, cooling the mixture to induce phase separation of the polymer from the components causes the formation of elongated polymer elements, such as polymer fibrils, as described elsewhere. In some embodiments, the polymer fibrils have an anisotropic distribution of fibril orientations. In some embodiments, each fibril of some of the plurality of polymer fibrils (e.g., a majority of the polymer fibrils) generally extends along the elongation direction from at least a first particle of one of the plurality of particles beyond the next-nearest neighbor of the first particle along the fibril.

[0078] In some embodiments, the particles are brittle and applying a first pressure to the mixture does not crack or break more than 5% of the particles. In some embodiments, the first release liner includes a first release surface 761, and separating the mixture from at least one of the first and second release surfaces includes removing the first release liner.

[0079] 8 is a schematic diagram of a method of making a film 800. The method includes providing (e.g., in a slurry or mixture 860) a plurality of particles, a polymer, and a component that is a solvent for the polymer at a second, higher temperature, but not a solvent for the polymer at a first, lower temperature. The method further includes extruding (e.g., using a pump 880) the plurality of particles, polymer, and component into a stream 870 at the second temperature. In some embodiments, a first release liner 861 and a second release liner 862 are provided, a gapped nip roller 883 and an alignment unit 881 are used to form a stream between the release liners 861 and 862, and an oven 884 is used to heat the stream to a second temperature. The method further includes passing the stream 870 through a nip 872 and cooling the stream to a first temperature (e.g., 874) to induce phase separation of the polymer from the component, where the nip 872 applies pressure to the stream before or during the phase separation. It has been found that if a nip is applied prior to (e.g., immediately prior to) or during phase separation, the shear and / or flow pattern of the resulting stream results in elongated polymeric elements (e.g., polymeric microfibrils) that are formed and substantially aligned as described elsewhere herein. Cooling can simply involve, for example, removing stream 870 from oven 884. Alternatively, a chill roll may be used. In some embodiments, nip 872 includes, for example, a chill roll. In some embodiments, the method further includes removing at least one of the liners (e.g., liner 861 shown diagrammatically in FIG. 8) and then removing the components (e.g., via oven drying in oven 885 as diagrammatically shown in FIG. 8). In some embodiments, second liner 862 is then removed to provide film 800, which may be wound into a roll 866 of film 800.

[0080] In some embodiments, film 800 includes a polymer and a plurality of particles dispersed therein at a volumetric capacity of greater than about 50 percent, or in any of the ranges described elsewhere. In some embodiments, the ratio of the volume of the plurality of particles to the volume of the polymeric material in film 800 is at least 4, or the ratio can be in any of the ranges described elsewhere. In some embodiments, protective outer layers are added to film 800 on both sides of the film to provide a multi-layer film. This can be done in the continuous process of FIG. 8 before winding the film into roll 866, or can be done in a separate manufacturing process, for example.

[0081] In some embodiments, extruding the plurality of particles, polymer, and ingredients into a stream at the second temperature includes extruding the stream into a first release liner 861 and applying a second release liner 862 onto the stream opposite the first release liner 861 before passing the stream through the nip. In some embodiments, the method further includes removing at least one of the first and second release liners after the cooling step and then removing at least a portion of the ingredients to provide a film.

[0082] 8 is performed without including particles in the slurry or mixture 860. In some embodiments, a method of producing a film including a polymer includes providing a component that is a solvent for the polymer at a second temperature higher than a first temperature and that is not a solvent for the polymer at the first temperature, extruding the polymer and the component into a stream at the second temperature, passing the stream through a nip, and cooling the stream to the first temperature to induce phase separation of the polymer from the component such that elongated polymer elements (e.g., polymer fibrils) having an anisotropic orientation distribution are formed, where the nip applies pressure to the stream before or during the phase separation, and cooling to induce.

[0083] In some embodiments, a method for producing a film comprising a plurality of elongated polymer elements interconnecting a plurality of particles includes the step of: 4 The method includes providing a polymer having a number average molecular weight of greater than 1 g / mol (or in any of the ranges described elsewhere) and a component that is a solvent for the polymer at a higher, second temperature but not at a lower, first temperature; forming a layer comprising a plurality of particles dispersed in a miscible solution of the polymer and the component (e.g., in some embodiments, 760 shown in FIG. 7C or 860 shown in FIG. 8); and inducing phase separation of the polymer from the component while the layer is under pressure (e.g., in some embodiments, the step shown in FIG. 7E or passing the stream through a nip 872 as shown in FIG. 8) such that the polymer forms a plurality of elongated polymer elements.

[0084] The higher second temperature and the lower first temperature referred to in any of the methods described herein can be any suitable temperature at which the component is a solvent for the polymer at the higher second temperature but is not a solvent for the polymer at the lower first temperature. The first temperature can be, for example, room temperature (e.g., 25°C). The second temperature can be, for example, in the range of 60°C to 200°C, or 80°C to 160°C. EXAMPLES

[0085] All parts, percentages, ratios, etc. in the examples and elsewhere herein are by weight unless otherwise indicated. The following abbreviations are used herein: RM = raw material, mBar = millibar, degC = °C, mins = minutes, hrs = hours, mg = milligrams, N = Newtons, s = seconds, nm = nanometers, kV = kilovolts, nA = nanoamperes, psi = pounds per square inch, N / s = Newtons / second, kPa = kilopascals.

[0086] [Table 1]

[0087] Example 1 4 g of GB32HS was weighed into a 30 g mixing container using an analytical balance. 1.0 g of UHMWPE was added to the container and the powders were thoroughly mixed by hand. Using a plastic pipette, 7.65 g of Isopar-G was added to the mixed solid powders. The solid-liquid mixture was then charged into a Speed ​​Mixture and mixed with the profile shown in Table 1.

[0088] [Table 2]

[0089] The homogenous mixture of GH32HS, UHMWPE, and Isopar-G was then slightly spread in an oval shape on a liner approximately 25.4 cm x 20.3 cm placed on a thick glass plate. A second liner of similar dimensions was layered on top of the oval mixture. The mixture was then spread uniformly along the length, between the two liners, and along the long axis of the oval using a notch bar set at a gap of approximately 0.9 mm. The opening of the notch bar was wider than the width of the liner used, so the combined thickness of the wet film and liner was measured by the gap of the notch bar. The film between the liners was carefully and gently transferred to the center of a 30 cm x 30 cm stainless steel plate. Four 30 cm x 30 cm gaskets, each 207.5 μm thick with a 22.86 cm x 22.86 cm opening in the center, were layered on top of the liner with the wet film in the center. A second stainless steel plate was placed on top of the gaskets. The stack between the two stainless steel plates was then transferred to the lower platen of a hot press. The platen temperature was maintained at 135°C. The gap between the upper and lower platens of the hot press was maintained at 5.5 mm by using a paint stick between them. In this configuration, the upper platen did not apply pressure to the stainless steel plate, but created a small heating chamber defined by the thickness of the paint stick. After melting the UHMWPE at 135°C for 10 minutes, the lower platen was lowered, the paint stick was quickly removed, the platens were stuck together, and 15 tons of pressure was applied to the stainless steel plate for 5 minutes. In this configuration, the gap between the stainless steel plates, and therefore the total thickness of the molten mass and liner, was measured by the total gasket thickness (830 μm). After 5 minutes, the lower platen was lowered and the entire stack including the stainless steel plate was transferred to the cold platen of the hot press and pressed against the weight of the platen for approximately 2 minutes. After 2 minutes, the stack was removed from the hot press, the liners were removed, and the composite film (formed between the two liners) was dried in a room environment by hanging it in a chemical fume hood for 18 hours. The film was dried in an oven at 90° C. for 30 minutes to remove any additional residual solvent.The average thickness of the resulting film, measured by micrometer at five different locations, was about 0.6 mm. The method for producing the film of Example 1 is shown generally in Figures 7A-7F.

[0090] Example 2 The sample of Example 2 was prepared using the same method as Example 1, except that 2.501 g of dry GBK1 powder was thoroughly hand mixed with 0.453 g of UHMWPE and 12.374 g of Isopar-G was added. The height of the notch bar was increased to 1.44 mm. The thickness of the gasket was increased to 1.2 mm by stacking five 207.5 μm thick gaskets and one 162.5 μm thick gasket. The mixing profile used is shown in Table 2. The average thickness of the resulting film, measured by micrometer at five different locations, was about 1.00 mm.

[0091] [Table 3]

[0092] Example 3 The sample of Example 3 was prepared using the same method as Example 1, except that 11.0 g of dry cenosphere powder was thoroughly hand mixed with 1 g of UHMWPE and 15 g of Isopar-G was added. The mixing profile used is shown in Table 2. The average thickness of the resulting film, measured by micrometer at five different locations, was about 0.69 mm.

[0093] Comparative Example C1 4g of GH32HS was weighed into a 30g mixing container using an analytical balance. 1.0g of UHMWPE was added to the container and the powders were thoroughly mixed by hand. On top of the mixed solid powders, 7.65g of Isopar-G was added using a plastic pipette. The solid-liquid mixture was then charged into a Speed ​​Mixture and mixed with the profile shown in Table 1.

[0094] The homogenous mixture of GH32HS, UHMWPE, and Isopar-G was then slightly spread in an oval shape on a liner approximately 25.4 cm x 20.3 cm that was placed on a thick glass plate. A second liner of similar dimensions was layered on top of the oval mixture. The mixture was then spread uniformly along the length, between the two liners, and along the long axis of the ellipse using a notch bar set at a gap of 0.9 mm. The opening of the notch bar was wider than the width of the liner used, so the combined thickness of the wet film and liner was measured by the gap of the notch bar. The wet film between the two liners was gently transferred to an aluminum pan and placed in a 135°C oven for 15 minutes. After 15 minutes, the sample was removed from the oven and quenched to room temperature by alternately touching both sides to the surface of a laboratory bench. After the sample had cooled, the two liners were peeled off and the composite film was dried in an ambient environment by hanging it in a laboratory chemical fume hood for 18 hours. The film was dried in an oven at 90° C. for 30 minutes to remove any additional residual solvent. The sample was then cut into two equal halves. One half was used as Comparative Example C1 and the other half was used as the input material for Comparative Example C2. The average thickness of the resulting film, measured by micrometer at five different locations, was about 0.89 mm.

[0095] Comparative Example C2 The other half of the sample of Comparative Example C1 was placed between two 25.4 cm x 20.3 cm liners. The film between the liners was gently transferred to the center of a 30 cm x 30 cm stainless steel plate. Four 30 cm x 30 cm gaskets, 207.5 μm thick, each with a 22.86 cm x 22.86 opening in the center, were layered on the liners with the wet film in the center. A second stainless steel plate was placed on top of the gaskets. The stack between the two stainless steel plates was then transferred to the lower platen of a hot press. The platen was maintained at 135°C. The gap between the upper and lower platens of the hot press was maintained at 5.5 mm by using a paint stick between them. In this configuration, the upper platen did not apply pressure to the stainless steel plate, but created a small heating chamber defined by the thickness of the paint stick. After softening the UHMWPE at 135°C for 10 minutes, the lower platen was lowered, the paint stick was quickly removed, the platens were attached, and 15 tons of pressure was applied to the stainless steel plates for 5 minutes. In this configuration, the gap between the stainless steel plates, and therefore the total thickness of the molten mass and liner, was measured by the total gasket thickness (830 μm). After 5 minutes, the lower platen was lowered and the entire stack including the stainless steel plates was transferred to the cold platen of the hot press and pressed down by the weight of the platens alone for about 2 minutes. After 2 minutes, the stack was removed from the hot press, the liners were removed, and the composite film between the liners was removed. The average thickness of the resulting film, measured by micrometer at five different locations, was about 0.63 mm.

[0096] Comparative Example C3 The sample of Comparative Example C3 was prepared using the same method as Comparative Example C1, except that 2.499 g of dry GBK1 powder was thoroughly hand mixed with 0.451 g of UHMWPE and 12.5 g of Isopar-G was added. The notch bar height was increased to 1.44 mm. The mixing profile used is shown in Table 2. The average thickness of the resulting film, measured by micrometer at five different locations, was approximately 1.22 mm.

[0097] Comparative example C4 The sample of Comparative Example C4 was prepared using the same method as Comparative Example C1, except that 11 g of dried cenosphere powder was mixed with 1.0 g of UHMWPE and 15 g of Isopar-G was added. The notch bar height was increased to 1.44 mm. The mixing profile used is shown in Table 2. The average thickness of the resulting film, measured by micrometer at five different locations, was about 0.72 mm.

[0098] Example 4 16.256g of GBS32HS was weighed into a 100g mixing container using an analytical balance. 4.064g of UHMWPE was added to the container and the powders were thoroughly mixed by hand. Using a plastic pipette, 30.09g of Isopar-G was added to the mixed solid powders. The solid-liquid mixture was then charged to a Speed ​​Mixture and mixed using the profile shown in Table 3.

[0099] [Table 4]

[0100] The homogenous mixture of GBS32HS, UHMWPE, and Isopar-G was then slightly spread into an oval shape on a liner approximately 25.4 cm by 25.4 cm placed on a thick glass plate. A second liner of similar dimensions was layered on top of the oval mixture. The mixture was then uniformly spread along the length, between the two liners, and along the long axis of the ellipse using a notch bar set at a gap of approximately 2.8 mm. The film between the liners was gently transferred to the center of the 1 mm thick spacer. A second 0.6 mm thick spacer was layered on top of the first spacer, with the liner between the two. A second stainless steel plate was placed on top of the second stainless steel spacer. The stack between the two stainless steel plates was then transferred to the lower platen of a hot press. The platen temperature was maintained at 135°C. The gap between the upper and lower platens of the hot press was maintained at 5.5 mm by using a paint stick between them. In this configuration, the upper platen did not apply pressure to the stainless steel plate, but created a small heating chamber defined by the thickness of the paint stick. After melting the UHMWPE at 135°C for 10 minutes, the lower platen was lowered, the paint stick was quickly removed, the platens were stuck together, and 15 tons of pressure was applied to the stainless steel plate for 5 minutes. In this configuration, the gap between the stainless steel plates, and therefore the total thickness of the molten mass and liner, was determined by the total thickness of the spacers and the thickness of the two liners between the spacers. After 5 minutes, the lower platen was lowered and the entire stack, including the stainless steel plate, was transferred to the cold platen of the hot press and pressed against the weight of the platen for approximately 2 minutes. After 2 minutes, the stack was removed from the hot press, the liners were removed, and the composite film was dried in a room environment by hanging in a chemical fume hood for 18 hours. The film was dried in an oven at 90°C for 30 minutes to remove any residual solvent. This resulted in a film thickness of approximately 1.75 mm as measured by a micrometer.

[0101] Example 5 The sample of Example 5 was prepared as described in Example 4, except that the dry film was laminated between two 40 μm thick polyolefin films using a laminator with the top roll maintained at about 88° C. The gap between the two nip rolls was maintained so that the nip rolls just touched the films when laminated without applying excessive pressure. The total thickness of the laminated film was about 1.8 mm, as measured with a micrometer.

[0102] Example 6 6.4g of GB32HS was weighed into a 30g mixing container using an analytical balance. 1.6g of UHMWPE was added to the container and the powders were thoroughly mixed by hand. Using a plastic pipette, 12.24g of Isopar-G was added to the mixed solid powders. The solid-liquid mixture was then charged to a Speed ​​Mixture and mixed using the profile shown in Table 1.

[0103] The homogenous mixture of GB32HS, UHMWPE, and Isopar-G was then slightly spread into an oval shape on a liner approximately 25.4 cm x 20.3 cm placed on a thick glass plate. A second liner of similar dimensions was layered on top of the oval mixture. The mixture was then spread uniformly along the length, between the two liners, and along the long axis of the oval using a notch bar set at a gap of approximately 1.44 mm. The opening of the notch bar was wider than the width of the liner used, so the combined thickness of the wet film and liner was measured by the gap of the notch bar. The film between the liners was gently transferred to the center of a 30 cm x 30 cm stainless steel plate. Five 30 cm x 30 cm gaskets, each 207.5 μm thick with a 22.86 cm x 22.86 cm opening in the center, and one 162.5 μm thick gasket were layered on the liner with the wet film in the center. A second stainless steel plate was placed on top of the gaskets. The stack between the two stainless steel plates was then transferred to the lower platen of a hot press. The platen temperature was maintained at 135°C. The gap between the upper and lower platens of the hot press was maintained at 5.5 mm by using a paint stick between them. In this configuration, the upper platen did not apply pressure to the stainless steel plate, but created a small heating chamber defined by the thickness of the paint stick. After melting the UHMWPE at 135°C for 10 minutes, the lower platen was lowered, the paint stick was quickly removed, the platens were stuck together, and 15 tons of pressure was applied to the stainless steel plate for 5 minutes. In this configuration, the gap between the stainless steel plates, and therefore the total thickness of the molten mass and liner, was measured by the total gasket thickness (830 μm). After 5 minutes, the lower platen was lowered and the entire stack including the stainless steel plate was transferred to the cold platen of the hot press and pressed against the weight of the platen for approximately 2 minutes. After 2 minutes, the stack was removed from the hot press, the liner was removed, and the composite film was dried in a room environment by hanging in a chemical fume hood for 18 hours. The film was dried in an oven at 90° C. for 30 minutes to remove any additional residual solvent. This resulted in a film thickness of approximately 900 μm, as measured with a micrometer.

[0104] Example 7 The sample of Example 7 was prepared as described in Example 6, except that the dry film was laminated between two 40 μm thick polyolefin films using a laminator with the top roll maintained at about 88° C. The gap between the two nip rolls was maintained so that the nip rolls just touched the films when laminated without applying excessive pressure. The thickness of the laminated film was about 950 μm, as measured with a micrometer.

[0105] Example 8 The sample of Example 8 was prepared as described in Example 4, except that 6.247 g of GBK1 dry powder and 2.006 g of UHMWPE were thoroughly mixed, and then 30.658 g of Isopar-G was added to the mixing vessel. The notch bar was set at a gap of about 1.42 mm. The resulting film was about 1.4 mm thick as measured with a micrometer.

[0106] Example 9 The sample of Example 9 was prepared as described in Example 8, except that the dry film was laminated between two 40 μm thick polyolefin films using a laminator with the top roll maintained at about 88° C. The gap between the two nip rolls was maintained so that the nip rolls just touched the films when laminated without applying excessive pressure. The thickness of the laminated film was about 1.53 mm, as measured by a micrometer.

[0107] Test Method and Results 1. TGA Test Small disks of a few millimeters in diameter were punched out and weighed so that the total mass of two to three disks ranged from 5 to 12 mg. Three samples of each of Example 1, Comparative Example C1, and Comparative Example C2 were loaded into an aluminum TGA pan and the temperature was increased from 35° C. to 550° C. at a rate of 4° C. / min in a nitrogen environment. The loss in weight of the samples as a function of temperature was recorded. All three samples showed very similar weight loss trends as a function of temperature. Table 4 shows the mass loss at 475° C. for all three samples. The data shows that all samples have similar polymer content.

[0108] [Table 5]

[0109] 2. Visual and SEM examination The samples were coated with a gold-palladium film approximately 10 nm thick before being loaded onto the stage of the SEM1. SEM images were taken at 10 kV and 0.4 nA current at various magnifications to capture the sample uniformity, distribution of polymer microfibrils, and morphology. The same method was used to take SEM images on both sides of each sample.

[0110] Visually, each of Examples 1-3 had a smooth surface on both sides with a glossy appearance. Comparative Examples C1 and C3-C4 had a very rough surface (some of the particles adhered to the liner when they were peeled off), and the film of Comparative Example C2 had a moderately smooth surface.

[0111] Macroscopically, the SEM images showed that the film from Example 1 had a uniform distribution of glass bubbles. Although some small dark spots were observed, the distribution of glass bubbles was very uniform. The film from Comparative Example C2 had macroscopic pits, some of which were 100 μm by 50 μm in size. The film from Comparative Example C2 still showed some macroscopic pits that were smaller in size and number than Comparative Example C1.

[0112] At the microscopic level, the SEM images showed that the film of Example 1 exhibited a uniform distribution of UHMWPE polymer microfibrils. The polymer microfibrils retained the GB32HS particles in the bulk and on the surface. The polymer microfibrils also exhibited what appeared to be a flow-induced anisotropic morphology. The magnified SEM images of Comparative Example C1 showed that the glass bubbles were less densely packed. The UHMWPE polymer particles were dissolved in the solvent, but in the absence of active mixing / flow, there may have been a local concentration gradient in the solvent when phase separation occurred. The resulting polymer phase reflected this local concentration gradient. Thus, there were local spots with higher UHMWPE, resulting in underutilization of the polymer available for bonding. This led to a mechanically weaker film, or the need for a higher polymer content to achieve the same mechanical performance. The bonding of the glass bubbles was also non-uniform. This could have caused some of the particles to migrate to the liner, which remains behind the macroscopic pits mentioned above. The SEM images of Comparative Example C2 showed a very different morphology. First, although the gasket used for compression was the same as that used to prepare Example 1, some of the glass bubbles broke. This indicated that the glass bubbles did not rearrange in the UHMWPE matrix as in the slurry of UHMWPE in Isopar-G. This conclusion was also supported by the observation that the lateral expansion of the samples was not as high as that of Example 1. Second, the polymer morphology also appeared very different. The polymer microfibrils on the surface of the glass bubbles appeared to shrink or fuse to form larger fibrils or microfilms. The fused polymer fibrils still contributed to the overall mechanical strength of the film, but the reprocessed microfibrils on the glass bubbles did not contribute to the bonding of the glass bubbles, resulting in a mechanically weaker film.

[0113] To understand the morphological differences between the examples and comparative examples, approximately 4" x 6" samples of each of Examples 1-3 and Comparative Examples C1, C3, and C4 were analyzed. SEM samples were cut from nine different spots (eight on the periphery and one in the center) of the 3x3 matrix covering the samples. A clear anisotropic distribution of polymer fibrils was observed in all examples. The fibrils were substantially radially oriented in each section of the 3x3 matrix such that the fibrils extended in substantially the same direction away from the central section. SEM images from the top central portion of the 3x3 matrix and from the bottom left corner portion of the 3x3 matrix are shown in Figures 8 and 9, respectively. The polymer fibrils of the comparative examples did not exhibit a preferred orientation distribution.

[0114] Small samples of 0.5 cm x 0.5 cm were cut from both Example 4 and Example 5 and placed on the sample stage of SEM2. Optical images of the samples were taken without any additional metal coating using the SEM operating in EDX mode. The SEM images showed that in the unlaminated film (Example 4), the glass bubbles were held together with the polymer microfibrils. The SEM images of the laminated film after careful removal of the polyolefin film still show that the glass bubbles were held together by the polymer microfibrils and that the glass bubbles were not destroyed during the lamination process.

[0115] 3. Capillary Flow Porometry Test Capillary flow porometry is a commonly used technique to characterize the pore size distribution and maximum pore size in porous membranes. A 25 mm diameter disk was cut and the mass was measured using an analytical balance. The thickness of the disk was measured using a 50.3 kPa thickness gauge and a 1.6 cm diameter flat anvil with a dwell time of approximately 3 seconds and a resolution of + / - 0.0001 inches. The sample was inserted into the capillary porometer. The sample was then tested using the default software parameters and running a 0-50 psi dry-up / wet-up test. A surface energy of 15.6 dynes / cm was used as the surface energy of the wetting fluid. After the dry test was completed, the software prompted to wet the sample. The sample holder was opened and wetting fluid FC-43 was dispensed onto the sample to completely fill and wet the pores. The sample holder was then closed and the wet test continued. The software then summarized the pressure and flow data and reported the bubble point pressure in pounds per square inch (psi) and the bubble point pore size in μm. This technique was a modification of ASTM F316-03(2006) "Standard Test Methods for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test."

[0116] The measured bubble point pressures and bubble point diameters for Example 1, Comparative Example C1, and Comparative Example C2 are shown in Table 5.

[0117] [Table 6]

[0118] These capillary flow porometry test results show that the film from Example 1 had the highest (lowest) bubble point pressure (bubble point diameter), indicating a more uniform small pore distribution in the sample. Comparative Example C1, prepared using a conventional coating method, had the lowest (highest) bubble point pressure (bubble point diameter), indicating the largest pores, confirming the observations from the SEM tests.

[0119] 4. Tensile Test Tensile tests of Examples 1 to 3 and Comparative Examples C1 to C4: Dogbone shaped samples measuring 12.0 cm in length and 2.45 cm in width were die cut from each of the composite films of Examples 1-3 and Comparative Examples C1-C4. The narrow portion of the sample in the center was 2.45 cm in length and 1.5875 cm in width. The samples were mounted between the two jaws of an Instron instrument 5.08 cm apart. With the lower jaw fixed, the upper jaw was moved to stretch the sample while applying a constant force on the sample at a rate of 5 N / s until the sample broke and the load reached a lower threshold of 0.5 N. The force required to break the sample was recorded as the maximum load, and the total stretch in the sample was also recorded. Table 6 shows the measured maximum force at break and stretch at break for the samples tested.

[0120] [Table 7]

[0121] Tensile testing of Examples 6 and 7: Dogbone shaped samples measuring 12.0 cm in length and 2.45 cm in width were die cut from the films of Examples 6 and 7. The narrow portion of the sample in the center was 2.45 cm in length and 1.5875 cm in width. The samples were mounted between two jaws of an Instron instrument spaced 5.08 cm apart. With the lower jaw fixed, the upper jaw was moved to stretch the sample while applying a constant force on the sample at a rate of 1 N / s until the sample broke and the load reached a lower threshold of 0.5 N. The force required to produce a particular extension was recorded as a function of extension. The tensile strength was calculated by dividing the force by the cross-sectional area of ​​the sample at the dogbone, and the tensile strain was calculated by dividing the extension by the spacing between the jaws. Table 11 shows the tensile test results.

[0122] The results from the tensile test show that the laminated film (Example 7) has a higher breaking strength and higher elongation at break (ie, better mechanical performance) than the unlaminated film (Example 6).

[0123] 5. Bending test: Bending tests of Examples 1 to 3 and Comparative Examples C1 to C4: Bend tests were performed using a cylindrical mandrel. Sample pieces 4 cm long and 2.0 cm wide were cut from each of Examples 1-3 and Comparative Examples C1-C4. Instead of a test panel, a glass microscope slide 7.6 cm long, 2.54 cm wide, and 1.5 mm thick was secured between the mandrel and the bent piece using clamping jaws and extended 0.8 cm toward the mandrel. The test sample film was attached to the end of the glass piece along its width with Kapton tape covering 0.4 cm of the sample film. With the handle in the vertically lowered position, the top surface of the bent piece was level with the top surface of the glass slide and the sample film was gently stretched to fit snugly between the mandrel and the bent piece. Starting with a 16 mm diameter mandrel, the test sample was bent around the mandrel by quickly lifting the handle to approximately 180 degrees. The film was visually evaluated for signs of cracking. The bending plate was lifted from the mandrel from which the test film was peeled off, and the handle was lowered in a vertical position. The mandrel was replaced with a smaller diameter mandrel, the alignment method was repeated, the same test sample was bent, and the mechanical condition of the test sample was recorded. This method was repeated with a variety of mandrels ranging in diameter from 16 mm to 2 mm, and the mandrel diameter at the onset of cracking and failure of the sample was recorded. This method was repeated with at least two samples for each example.

[0124] Bending test of Examples 4 to 9: Bend tests were performed using a cylindrical mandrel. From Examples 4 and 5, strips were cut that were 2.54 cm wide by 8.4 cm long. From Examples 6 and 7, films were cut that were 10.16 cm long by 2.54 cm wide. To avoid pressure on the sample from the clamping jaws, the sample strip was placed under the clamping jaws and secured along its width with Kapton tape covering approximately 1 cm of the sample film. With the handles in the vertically lowered position, the top of the bend strip was level with the top of the clamping surface and the sample film was gently stretched to fit snugly between the mandrel and the bend strip. Starting with a 16 mm diameter mandrel, the test sample was bent around the mandrel by quickly lifting the handles to approximately 180 degrees. The films were visually evaluated for signs of cracking. The bend plate was lifted off the mandrel from which the test film was peeled off and the handles were lowered in the vertical position. The mandrel was replaced with a smaller diameter mandrel, the alignment method was repeated, the same test sample was bent, and the mechanical condition of the test sample was recorded. This method was repeated with a variety of mandrels ranging in diameter from 16 mm to 2 mm. The mandrel diameter at the onset of cracking and failure of the sample was recorded. This method was repeated with at least two samples for each example. The results of the bend test show that the film samples laminated between polyolefin films showed a significant improvement in bend performance.

[0125] The results of the bending tests are summarized in Table 7.

[0126] [Table 8]

[0127] 6. Complex dielectric constant test Depending on the frequency range of interest, two different dielectric constant tests were used to measure the dielectric constant of glass bubble-filled films prepared with different glass bubbles.

[0128] Split Post Resonator (SPR) Dielectric Test: The complex permittivity (dielectric constant and dielectric loss tangent) was measured using two separate dielectric split-post resonators specially designed for the measurements at two frequencies, 2.5 GHz and 9.5 GHz. These cavities and the calculation software were obtained from QWED Company (Warsaw, Poland). The resonant bandwidth and the resonant frequency of the appropriate cavity resonance (defined in terms of the nominal cavity frequency) were both determined by S 21 The magnitude of the transmission S-parameter, defined as: was precisely measured using each cavity with no sample inserted (four measurements). S 21 These electronic measurements were each performed using a two-port measurement with a VNA-KS. Using the four electronic measurements above and the sample thickness measurement, the complex permittivity was calculated using QWED software at each frequency for each cavity.

[0129] Free Space Permittivity Test: A simple free-space measurement system designed and built by Thomas Keating Ltd (Billingshurst, United Kingdom) was implemented to determine the dielectric constant of samples at high frequencies. This free-space system was coupled with a Vector Network Analyzer (VNA) and analysis software to allow the determination of complex material properties including the transmission of power through the material at any angle of incidence between 0 and 60 degrees. This system, from Thomas Keating, is a 60-90 GHz quasi-optical system, i.e. the size of the optical components is small relative to the wavelength, thereby necessitating the use of geometric optics to design such a system.

[0130] The Keysight VNA hardware is a "zero gain" circuit whereby a Gaussian beam waist at the aperture of a corrugated feed horn connected to one port is refocused by an ellipsoidal mirror to form a beam waist at the sample location, then passed via a second mirror to the second port where a second corrugated feed horn delivers the beam into the VNA waveguide. The measurements are performed using the complex S-parameters S 21 and S11 The PNA-KS was used directly for transmission and reflection measurements as the normalized power related to the complex S-parameter S 21 and S 11 Calculations of the complex permittivity (dielectric constant and dielectric loss) from were performed using Keysight analysis software using the standard NIST (National Institute of Standards and Technology) method as described in NIST Technical Note 1355R.

[0131] The dielectric constants of various samples measured at different frequencies with corresponding test methods are shown in Table 8.

[0132] [Table 9]

[0133] FIG. 12 shows the change in dielectric constant in the frequency range of 60 to 90 GHz measured using the free space dielectric constant test method.

[0134] The results from the complex dielectric constant tests show that the dielectric constant and dielectric loss of the laminated samples are very low and similar to the unlaminated samples.

[0135] Transmission Loss Test: To demonstrate the potential use of low permittivity, low loss materials in high frequency electromagnetic applications, scattering parameters or S-parameters were measured in an anechoic chamber with two horn antennas mounted 400 mm apart at the centre of a precision optical slide mount. A rotating sample stage was mounted on an optical rail between the two antennas so that its position could be varied relative to the antennas. The source and receive antennas were actuated using the source and receive modules, respectively. A copper plate with a 50 mm x 50 mm opening was mounted on the sample holder between the two antennas. The sample was held flush with the copper plate with mounting screws and a plastic bar to act as a clamp. The distance of the sample from the source antenna and the orientation of the sample relative to the axis of the optical rail were varied. The high frequency electromagnetic signal was fed from the VNA-RS to the source module. The transmitted signal received by the receive antenna was filtered through the receive module and then fed to the VNA-RS. The reflected and transmitted signals were then recorded at normal incidence when the sample was 200 mm away from the source antenna. After equilibrating the instrument against thermal fluctuations, an air measurement (i.e., no sample) was taken at each position / angle combination for reference and subtracted from the actual sample data set. The data are the S 21 The parameters (transmission coefficients) were collected to provide information on the transmission coefficients. Three samples were prepared using TPO (3.0 mm thickness, ε′ of 2.46), PX5008 (0.8 mm thickness, ε′ of 2.04), and Glass Bubbles films (Examples 1 and 2) to test the effectiveness of the films prepared using the above method in suppressing early reflections of automotive radar signals, for example, at bumpers, as shown in Table 9:

[0136] [Table 10]

[0137] The measured transmission loss as a function of frequency in the 77 GHz band (76-81 GHz) used for automotive radar is shown in FIG. 13. These results show that the transmission loss of TPO alone, a plastic material commonly used in automotive bumpers, is the highest in the 77 GHz band. As the dielectric constant changes from TPO to the high radio wave transmission medium (air high), the transmission intensity also shows high amplitude fringes (ripples) due to early reflections at the bumper air interface. These fringes are responsible for the "ghost image" of the object of interest in front of the radar. In the same frequency range, the transmission loss was reduced when a three-layer structure formed by combining TPO with PX5008 and the film of Example 1 or Example 2 was used. Furthermore, when the film of Example 1 was applied to TPO, the amplitude of the early reflection fringes in the transmission curve was reduced. These results show that the (e.g., low dielectric constant, low loss) films described herein can be advantageously used as one of the layers in a multi-layer structure of bumper materials used in front of automotive radar.

[0138] EM modeling calculations for transmission / return losses: EM (electromagnetic) modeling for transmission loss and reflection loss was performed using Microwave Studio Simulation Tool. The same sample as above, control, Sample 1, and Sample 2 were modeled to calculate the transmission loss and reflection loss. The resulting transmission loss is shown in FIG. 14, and the resulting reflection coefficient is shown in FIG. 15. The measurement and modeling results for transmission loss are consistent as can be seen from FIG. 13 and FIG. 14. Sample 2 showed the most favorable performance in the frequency range of interest for radar applications. The thickness of the glass bubbles film used in the construction of Sample 2 (i.e., the thickness of the film of Example 2) was optimized and calculated using EM the Microwave Studio Simulation Tool. The transmission loss plot in FIG. 14 shows minimized variation, which means that the example film on TPO can minimize the reflection from the interface between TPO and air over the frequency range of interest. FIG. 16 shows the S 11(Reflection Coefficient) calculation results are shown. The control sample has the highest reflection variation according to frequency, and Sample 1 has less variation than the control sample. Sample 2 showed the lowest reflection variation from 72 to 82 GHz through optimization of the individual layer structure (e.g. thickness and refractive index) using the CST Microwave Studio Simulation Tool. This broadband characteristic of Sample 2 can provide tolerance to the variation of the dielectric constant and thickness of the bumper material. Therefore, the sample film can provide more freedom in the selection of bumper material / thickness and manufacturing tolerance.

[0139] Terms such as "about" will be understood by those of skill in the art in the context in which they are used and described herein. If the use of "about" as applied to quantities describing feature sizes, amounts, and physical properties is not clear to those of skill in the art in the context in which it is used and described herein, "about" will be understood to mean within 10 percent of the specified value. A quantity given as about a specified value may be the exact specified value. For example, if it is not clear to those of skill in the art in the context in which it is used and described herein, a quantity having a value of about 1 means that the quantity has a value between 0.9 and 1.1, and means that the value may be 1.

[0140] All references, patents, or patent applications referenced above are hereby incorporated by reference in their entirety. In the event of any inconsistency or contradiction between any portion of the incorporated reference and this application, the information in the foregoing description shall take precedence.

[0141] Descriptions of elements in a figure should be understood to apply equally to corresponding elements in other figures unless otherwise indicated. Although specific embodiments have been illustrated and described herein, those skilled in the art will appreciate that the specific embodiments illustrated and described may be replaced by various alternative and / or equivalent embodiments without departing from the scope of the present disclosure. This application is intended to cover any adaptations or variations of the specific embodiments discussed herein. Accordingly, it is intended that the present disclosure be limited only by the claims and their equivalents. The present invention includes the following aspects. (1) A film comprising a polymeric material and a plurality of particles dispersed therein, the polymeric material includes a plurality of elongated polymeric elements oriented along substantially the same first direction and interconnecting the particles; an elongated end portion of at least one first elongated polymeric element of the plurality of elongated polymeric elements conforms to and is bonded to a first particle of the plurality of particles along an entire length of the elongated end portion; an elongated intermediate portion of at least one second elongated polymeric element of the plurality of elongated polymeric elements conforms to and is bonded to a second particle of the plurality of particles along an entire length of the elongated intermediate portion; The second elongated polymeric elements extend from opposite ends of the elongated intermediate portion in a direction away from the second particles. (2) The film of item 1, wherein the particles of the plurality of particles are dispersed in the polymeric material at a volumetric capacity of greater than about 50 percent. (3) The film of any one of the preceding claims, wherein the particles of the plurality of particles are hollow and have an average size greater than about 1 micron. (4) A film comprising a polymeric material and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the polymeric material comprises a plurality of elongated polymeric elements interconnecting the particles; each elongated polymer element in a portion of the plurality of elongated polymer elements includes a plurality of spaced apart elongated portions; each of the plurality of spaced apart elongated portions conforming to and bonding with one of the plurality of particles along an entire length of the elongated portion; The polymer elements extend from both ends of the elongated portion in a direction away from the particles. 5. The film of claim 4, wherein the plurality of spaced apart elongated portions comprises at least three elongated portions. (6) The film according to item 4 or 5, wherein the ratio of the volume of the plurality of particles to the volume of the polymeric material is at least 5. (7) A multilayer film including a porous intermediate layer disposed between and bonded to opposing non-porous first and second protective layers, the porous intermediate layer comprising: a plurality of elongated polymer elements interconnecting a plurality of hollow particles; a plurality of interconnected voids defined by said plurality of elongated polymeric elements and hollow particles; and wherein the real part of the dielectric constant of the film at a frequency of about 2.5 GHz is less than about 1.4. (8) The multilayer film according to item 7, wherein the ratio of the imaginary part of the dielectric constant of the film to the real part at a frequency of about 2.5 GHz is less than about 0.004. (9) The multilayer film according to item 7 or 8, wherein the particles of the plurality of particles are dispersed in the porous intermediate layer at a volumetric capacity of greater than about 50 percent. (10) A multilayer film comprising an intermediate layer disposed between and bonded to opposing first and second protective layers, the intermediate layer comprises a plurality of elongated polymer elements interconnecting a plurality of particles; A multilayer film, wherein for at least one pair of first and second particles of the plurality of particles, and for each elongated polymer element in a portion of the plurality of elongated polymer elements, a first end of the element terminates at the first particle and an opposite second end of the element terminates at the second particle. 11. The multilayer film of claim 10, wherein the elongated polymer elements in the portion of the plurality of elongated polymer elements are substantially parallel to one another. (12) A multilayer film comprising an intermediate layer disposed between and bonded to opposing first and second layers, the intermediate layer comprises a plurality of hollow particles dispersed therein in a volumetric capacity of greater than about 50 percent; the multilayer film has an elongation at break of at least 15% at room temperature at a tensile loading rate of about 5 Newtons per second or less; A multilayer film, wherein bending the multilayer film at a bend location with an inside radius of up to 1.5 mm results in little or no damage to the intermediate layer at the bend location. (13) A method of producing a film, the film comprising a polymer and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the method comprising: providing a mixture at a first temperature, the mixture including the plurality of particles, the polymer, and a component that is a solvent for the polymer at a second higher temperature but is not a solvent for the polymer at the first lower temperature; disposing the mixture between first and second release surfaces; heating the mixture to the second temperature; applying a first pressure to the mixture; cooling the mixture to induce phase separation of the polymer from the components; and separating the mixture from at least one of the first and second release surfaces; The method of claim 1, wherein the mixture is under the first pressure at the second temperature for at least a first time interval before cooling the mixture, the first pressure being sufficiently high to cause the polymer to flow. (14) A method of producing a film, the film comprising a polymer and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the method comprising: providing said plurality of particles, said polymer, and a component that is a solvent for said polymer at a second higher temperature but is not a solvent for said polymer at a first lower temperature; extruding the plurality of particles, the polymer, and the component into a stream at the second temperature; passing said stream through a nip; and cooling the stream to the first temperature to induce phase separation of the polymer from the components, the nip applying pressure to the stream prior to or during the phase separation. (15) A method of producing a film, the film comprising a plurality of elongated polymer elements interconnecting a plurality of particles, the method comprising: The plurality of particles, about 10 4 providing a polymer having a number average molecular weight of greater than 100 g / mol and a component that is a solvent for said polymer at a second higher temperature but not at a first lower temperature; forming a layer comprising the plurality of particles dispersed in a miscible solution of the polymer and the component; and inducing phase separation of said polymer from said component while said layer is under pressure such that said polymer forms said plurality of elongated polymer elements.

Claims

1. A film comprising a polymeric material and a plurality of particles dispersed therein, the polymeric material includes a plurality of elongated polymeric elements oriented along substantially the same first direction and interconnecting the particles; an elongated end portion of at least one first elongated polymer element of the plurality of elongated polymer elements conforms to and is bonded to a first particle of the plurality of particles along an entire length of the elongated end portion; an elongated intermediate portion of at least one second elongated polymeric element of the plurality of elongated polymeric elements conforms to and is bonded to a second particle of the plurality of particles along an entire length of the elongated intermediate portion; The second elongated polymeric elements extend from opposite ends of the elongated intermediate portion in a direction away from the second particles.

2. 10. The film of claim 1, wherein the particles of the plurality of particles are dispersed in the polymeric material at a volumetric capacity of greater than about 50 percent.

3. 3. The film of claim 1 or 2, wherein the particles of the plurality of particles are hollow and have an average size greater than about 1 micron.

4. 1. A film comprising a polymeric material and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the polymeric material comprises a plurality of elongated polymeric elements interconnecting the particles; each elongated polymer element in a portion of the plurality of elongated polymer elements includes a plurality of spaced apart elongated portions; each of the plurality of spaced apart elongated portions conforming to and bonding with one of the plurality of particles along an entire length of the elongated portion; The polymer elements extend from both ends of the elongated portion in a direction away from the particles.

5. The film of claim 4 , wherein the plurality of spaced apart elongated portions comprises at least three elongated portions.

6. 6. The film of claim 4 or 5, wherein the ratio of the volume of the plurality of particles to the volume of the polymeric material is at least 5.

7. 1. A multi-layer film comprising a porous intermediate layer disposed between and bonded to opposing non-porous first and second protective layers, the porous intermediate layer comprising: a plurality of elongated polymer elements interconnecting a plurality of hollow particles; a plurality of interconnected voids defined by said plurality of elongated polymeric elements and hollow particles; and wherein the real part of the dielectric constant of the film at a frequency of about 2.5 GHz is less than about 1.

4.

8. 8. The multilayer film of claim 7, wherein the ratio of the imaginary part of the dielectric constant of the film to the real part at a frequency of about 2.5 GHz is less than about 0.

004.

9. 9. The multilayer film of claim 7 or 8, wherein the particles of the plurality of particles are dispersed in the porous intermediate layer at a volumetric capacity of greater than about 50 percent.

10. 1. A multi-layer film comprising an intermediate layer disposed between and bonded to opposing first and second protective layers, the intermediate layer comprises a plurality of elongated polymer elements interconnecting a plurality of particles; For at least one pair of first and second particles among said plurality of particles, and for each elongated polymer element in a portion of said plurality of elongated polymer elements, a first end of said element terminates at said first particle and an opposite second end of said element terminates at said second particle.

11. 11. The multilayer film of claim 10, wherein the elongated polymeric elements in the portion of the plurality of elongated polymeric elements are substantially parallel to one another.

12. 1. A multi-layer film comprising an intermediate layer disposed between and bonded to opposing first and second layers, the intermediate layer comprises a polymeric material and a plurality of hollow particles dispersed therein in a volumetric capacity of greater than about 50 percent; the polymeric material comprises a plurality of elongated polymeric elements interconnecting the particles; The multilayer film has an elongation at break of at least 15% at room temperature at a tensile loading rate of about 5 Newtons per second or less; A multilayer film, wherein bending the multilayer film at a bend location with an inside radius of up to 1.5 mm results in little or no damage to the intermediate layer at the bend location.

13. 1. A method of manufacturing a film, the film comprising a polymer and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the method comprising: providing a mixture at a first temperature, the mixture including the plurality of particles, the polymer, and a component that is a solvent for the polymer at a second temperature higher than the first temperature but is not a solvent for the polymer at the first temperature lower than the second temperature; disposing the mixture between first and second release surfaces; heating the mixture to the second temperature; applying a first pressure to the mixture; cooling the mixture to induce phase separation of the polymer from the components; and separating the mixture from at least one of the first and second release surfaces; The method of claim 1, wherein the mixture is under the first pressure at the second temperature for at least a first time interval prior to cooling the mixture, the first pressure being sufficiently high to cause the polymer to flow.

14. 1. A method of manufacturing a film, the film comprising a polymer and a plurality of particles dispersed therein in a volumetric capacity of greater than about 50 percent, the method comprising: providing the plurality of particles, the polymer, and a component that is a solvent for the polymer at a second temperature higher than a first temperature but is not a solvent for the polymer at the first temperature lower than the second temperature; extruding the plurality of particles, the polymer, and the component into a stream at the second temperature; passing said stream through a nip; and cooling the stream to the first temperature to induce phase separation of the polymer from the components, the nip applying pressure to the stream prior to or during the phase separation.

15. 1. A method of manufacturing a film, the film comprising a plurality of elongated polymer elements interconnecting a plurality of particles, the method comprising: The plurality of particles, about 10 4 providing a polymer having a number average molecular weight of greater than 100 g / mol and a component that is a solvent for said polymer at a second temperature higher than a first temperature but is not a solvent for said polymer at said first temperature lower than said second temperature; forming a layer comprising the plurality of particles dispersed in a miscible solution of the polymer and the component; and inducing phase separation of said polymer from said component while said layer is under pressure such that said polymer forms said plurality of elongated polymer elements.

Citation Information

Patent Citations

  • Resin molding

    JP1983093759A

  • Hot-melt seal material composition

    JP2001040330A

  • Liquid crystal polymer composition

    JP2017057258A

  • Easy-disassembly hot-melt composition

    JP2017179061A

  • Liquid-crystalline polymer composition containing nanostructured hollow-carbon material and molded article thereof

    US20090294729A1